2021
DOI: 10.1002/adfm.202008261
|View full text |Cite
|
Sign up to set email alerts
|

Bioprinting of Cartilaginous Auricular Constructs Utilizing an Enzymatically Crosslinkable Bioink

Abstract: Bioprinting of functional tissues could overcome tissue shortages and allow a more rapid response for treatments. However, despite recent progress in bioprinting, and its outstanding ability to position cells and biomaterials in a precise 3D manner, its success has been limited, due to insufficient maturation of constructs into functional tissue. Here, a novel calcium‐triggered enzymatic crosslinking (CTEC) mechanism for bioinks based on the activation cascade of Factor XIII is presented and utilized for the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 109 publications
1
37
0
Order By: Relevance
“…Previous studies, [27][28][29][30][31] reported a significant maturation of the HA-TG hydrogels in the first three weeks of culture due to the deposition of ECM from the cells leading to an increase in overall stiffness of the samples. Nevertheless, the very low stiffness of the HA-TG hydrogel reported at day one implies that implantation at this early stage could be at risk of failure.…”
Section: In Vitro Maturation and Mechanical Testing Of Ha-tg Hydrogels And Ha-tg Reinforced Hydrogelsmentioning
confidence: 94%
See 3 more Smart Citations
“…Previous studies, [27][28][29][30][31] reported a significant maturation of the HA-TG hydrogels in the first three weeks of culture due to the deposition of ECM from the cells leading to an increase in overall stiffness of the samples. Nevertheless, the very low stiffness of the HA-TG hydrogel reported at day one implies that implantation at this early stage could be at risk of failure.…”
Section: In Vitro Maturation and Mechanical Testing Of Ha-tg Hydrogels And Ha-tg Reinforced Hydrogelsmentioning
confidence: 94%
“…Semiquantitative Evaluation: Semiquantitative evaluation of the histological and immunohistological staining was performed as previously described. [27] Briefly, images were decomposed in channels in ImageJ (National Institutes of Health, USA, v1.52n) using color deconvolution. The channels represented the hematoxylin and DAB stain for Collagen I and Collagen II, while the hematoxylin and stain of glycosaminoglycans for the SafraninO staining.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The restricted application of bioprinting for bone implantation is related to its low resolution in the spatial material structure. An accurate scaffold width is momentous for in vivo investigations, such as in enzymatically cross-linkable materials, 54 neuron regeneration and connection, 55 and cell delivery. 56 This example suggests why precise control of the bone scaffold width plays a vital role in macroscopic organ function as well as in microscopic cell differentiation and growth.…”
Section: Bone Printing Process Controlmentioning
confidence: 99%